Politik Hukum Ekonomi Syariah Dalam Undang-Undang Cipta Kerja - Pirdayanti, Yupi; Shaleh, Chaerul; Nilda, Elvi (Jurnal Hukum Ekonomi Syariah : AICONOMIA, 2022)
Wage policy has an urgency that affects the operational aspects of the company's business. In addition, the issue of wages has become a sensitife matter among workers. This is because the wages earned by a worker represent the value of the worker. Islam as a religion of mercy for all nature, the principles of wages in the Islamic Economy include fair and worthy. This research will discuss the comparison between wages in the Job Creation Law and the politics of sharia economic law. This comparison will explain how the wage process is regulated in the Job Creation Law and wages based on sharia economic law. Research uses comparative descriptive methods to find differences and relevance in the implementation of Islamic law in the wage system. The results showed that both principles of wages in the Islamic economy have been implemented in wages in Indonesia even though some employers have not been able to provide eligibility for their workers.